Modelo de implementação da web semântica nas empresas - Ferreira, Reinaldo (2013)
The Semantic Web is an important challenge for today's Web usage. The progressive transformation of the Web based on documents into the Web based on data will bring up a Web scale database. Given that the Enterprise Semantic Web is still a less explored subject, this article proposes an Implementation Model that helps the introduction of the technology and the evaluation of its' impact in the applications used and tasks performed.